MOTIVASI PERNIKAHAN DI KALANGAN MAHASISWA S1 UNIVERSITAS RIAU - Arindya Yulia FR; Zulfan Saam; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to know the factors to motivate student to married while the students continue their study. The subject of this research is ten students have been married and still active in college. The research design was descriptive research design that use qualitative approach. The sample of this research were used snowball sampling. Research data is obtained through unfold interview and dokumentasion. The results of analysis shows that students motivation in marriage while continoued study were consist if 2 (two) categories from the theory of hygiene-motivator by Frederick Hezberg, such as intrinsic motivations and extrinsic. The intrinsic motivations such as : a) Avoid adultery, b) Match and need each other, c) The dream of people (based on Al-Qur’an surah Ar-Rum 21, d) Have age enough to mary, e) Biological needs, f) To get generation of family. For the more, extrinsic motivation are: a) Support from family, b) Reduce the burden on parents, c) Knowledge gained from taqlim assemblies.Keywords: College student, Marriage, Motivation